Fatores de risco e proteção e justiça restaurativa: a percepção de socioeducadores - Ferrão, Iara da Silva (2015)
The study aimed to investigate the perception of professionals on risk and protective factors when working with adolescents who are undergoing socioeducative measures (MSE) in inpatient treatment units and supervised outpatient work for adolescents in conflict with the law in a small city of Rio Grande do Sul state. It also sought to undestand how the practices of Restorative Justice (JR) can be perceived as potencial protective factors for adolescents who are in conflict with the law. To achieve the proposed objectives, a qualitative research was performed with the professionals working in the inpatient and outpatient units. For data collection we used a questionnaire with open and closed questions based on the literature review. To analyze the information of the data collected, open questions were submitted to thematic content analysis as proposed by Bardin. For analysis of the closed questions a statistical summary of variables was used. The data analysis revealed that the professionals notice different risk and protective factors in the lives of the adolescents in conflict with the law. In regard to knowledge of restorative practices, the majority of the professionals report to be aware of them but few indicate the ones they apply in their treatment units. In conclusion, we suggest the need to develop new studies, mainly on risk and protective factors at the individual level, which were the least considered aspects by the respondents.